The Regulation of Tax Imposition on Property Rights Acquisition For Foreign Citizens In Indonesia Post The Job Creation Law Number 6 of 2023 - Illona, Illona; Sally , Jeane Neltje (Eduvest - Journal of Universal Studies, 2023)
This article discusses the regulation of tax imposition on property rights acquisition for foreign nationals (foreigners) in Indonesia following the enactment of Law Number 6 of 2023 regarding Job Creation. Property is an asset that holds significant economic value in the growth of a country's economy. Foreign nationals seeking to acquire property rights in Indonesia also must pay taxes, such as Value Added Tax (VAT), Land and Building Acquisition Duty (BPHTB), and Land and Building Tax (PBB). Although the imposition of taxes on foreign nationals is similar to that for Indonesian citizens, this is done to enhance the attractiveness of investment in the Indonesian property sector. The regulation of tax imposition hasn't changed significantly following the enactment of the Job Creation Law. The most noticeable changes can be seen in VAT/VAT on Luxury Goods. Even though the regulations regarding tax imposition for foreign nationals haven't changed significantly after the Job Creation Law, alterations can be observed in the procedural implementation. After the Job Creation Law, foreign nationals only need a passport as a document requirement in the process of acquiring property rights in Indonesia. However, there are still obstacles in the regulation of tax imposition for foreign nationals, such as challenges in using a passport as a required document, ambiguity in the imposition of PBB on PBB objects, and validation of BPHTB payments. This diminishes the interest of foreign nationals in purchasing property in Indonesia.